Transcriptome analysis of filling stage seeds among three buckwheat species with emphasis on rutin accumulation - Gao, J.; Wang, T.; Liu, M.; Liu, J.; Zhang, Z. (Public Library of Science, 2017)
Buckwheat is an important minor crop with pharmaceutical functions due to rutin enrichment in the seed. Seeds of common buckwheat cultivars (Fagopyrum esculentum, Fes) usually have much lower rutin content than tartary buckwheat (F. tartaricum, Ft). We previously found a wild species of common buckwheat (F. esculentum ssp. ancestrale, Fea), with seeds that are high in rutin, similar to Ft. In the present study, we investigated the mechanism by which rutin production varies among different buckwheat cultivars, Fea, a Ft variety (Xide) and a Fes variety (No.2 Pingqiao) using RNA sequencing of filling stage seeds. Sequencing data generated approximately 43.78-Gb of clean bases, all these data were pooled together and assembled 180,568 transcripts, and 109,952 unigenes. We established seed gene expression profiles of each buckwheat sample and assessed genes involved in flavonoid biosynthesis, storage proteins production, CYP450 family, starch and sucrose metabolism, and transcription factors. Differentially expressed genes between Fea and Fes were further analyzed due to their close relationship than with Ft. Expression levels of flavonoid biosynthesis gene FLS1 (Flavonol synthase 1) were similar in Fea and Ft, and much higher than in Fes, which was validated by qRT-PCR. This suggests that FLS1 transcript levels may be associated with rutin accumulation in filling stage seeds of buckwheat species. Further, we explored transcription factors by iTAK, and multiple gene families were identified as being involved in the coordinate regulation of metabolism and development. Our extensive transcriptomic data sets provide a complete description of metabolically related genes that are differentially expressed in filling stage buckwheat seeds and suggests that FLS1 is a key controller of rutin synthesis in buckwheat species. FLS1 can effectively convert dihydroflavonoids into flavonol products. These findings provide a basis for further studies of flavonoid biosynthesis in buckwheat breeding to help accelerate flavonoid metabolic engineering that would increase rutin content in cultivars of common buckwheat.